HDPE Plastic Waste as a Fine Aggregate Substitute in the Production of CLC Lightweight Bricks: An Experimental Study - Mg, Taufiqurrahman; Nursyamsi, Nursyamsi; Tarigan, Johannes; Bakara, Ricky (Syntax Corporation, 2025)
This study aims to examine the utilization of High-Density Polyethylene (HDPE) plastic waste as a partial substitute for fine aggregate in the manufacture of Cellular Lightweight Concrete (CLC) lightweight bricks. The method used is a laboratory experiment with variations in the addition of HDPE of 0%, 5%, 10%, and 15% to the CLC mixture. Each variation was tested to determine the compressive strength, dry unit weight, and water absorption capacity after curing for 28 days. The results showed that the addition of HDPE affected the mechanical characteristics of lightweight bricks. The compressive strength decreased with increasing HDPE percentage, where the highest value was recorded at the 0% HDPE variation of 1.16 MPa and the lowest at the 15% variation of 0.92 MPa, below the SNI 8640-2018 standard. The highest dry unit weight was achieved at a composition of 5% HDPE of 3.32 kg/m³, indicating optimal density. However, the addition of HDPE also increased water absorption, with the highest average of 25.08% at the 15% variation. Thus, the use of HDPE waste as a substitute material shows environmentally friendly potential, but needs to be optimized so as not to reduce the structural quality of CLC lightweight bricks.